2017
DOI: 10.1149/2.0081704jss
|View full text |Cite
|
Sign up to set email alerts
|

Current Stage of the Investigation of the Composition of Oxygen Precipitates in Czochralski Silicon Wafers

Abstract: In this work, we look on the current stage of the investigation of the composition of oxygen precipitates obtained with the help of different techniques. Moreover, we present our recent and new investigation of the composition of oxygen precipitates carried out by means of energy dispersive X-ray spectroscopy, electron energy loss spectroscopy, and Fourier transform infrared spectroscopy. The FTIR spectra measured at liquid helium temperature are compared with the spectra simulated on the basis of experimental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 38 publications
1
8
0
Order By: Relevance
“…Such kind of dependence is expected for the ratio of the surface to total atom numbers of the precipitates and might be explained by the charge accumulation within the OP shells. This assumption is in agreement with the recent finding by Kot et al about core–shell OPs composition and structure and leads to the conclusion that charge accumulation localized in the shell of the precipitate due to broken SiO x bonds, whereas the SiO 2 core remains electrically neutral.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Such kind of dependence is expected for the ratio of the surface to total atom numbers of the precipitates and might be explained by the charge accumulation within the OP shells. This assumption is in agreement with the recent finding by Kot et al about core–shell OPs composition and structure and leads to the conclusion that charge accumulation localized in the shell of the precipitate due to broken SiO x bonds, whereas the SiO 2 core remains electrically neutral.…”
Section: Discussionsupporting
confidence: 92%
“…Numerous experimental data on the investigation of the composition and the structure of OPs collected by Vanhellemont [1] show that the OP composition can vary in different samples in wide ranges from SiO 1 to SiO 2 . Recent extensive studies of Kot et al with the help of Fourier-transform infrared spectroscopy (FTIR), [2] energy-dispersive X-ray spectroscopy (EDX), and electron energy loss spectroscopy (EELS), [3] jointly discussed in the previous study, [4] revealed that the composition of the OP is nonuniform: stoichiometric SiO 2 amorphous core is surrounded with the SiO x shell. Based on the core-shell structure of OPs, Vanhellemont [1] proposed a model that explains the variation of an average oxygen content for OPs of different shapes and sizes by the variation of the shell percentage.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the wide knowledge about oxide precipitation, the composition of oxide precipitates SiO x still remained unclear. This was due to the different x values published varying between x = 1 and x = 2 (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31). Skiff et al investigated plate-like precipitates by electron energy loss spectroscopy (EELS) in the near-edge and ionization edge range already in 1986 (21).…”
Section: Investigation Of the Stoichiometry Of Oxygen Precipitatesmentioning
confidence: 99%
“…This is, however, not the case for the EELS plasmon method. [8] In this method, the composition of the precipitates is determined from the deconvolution of the low loss EEL spectra into reference spectra of Si, SiO, and SiO 2 . For more detailed information, the reader is referred to Ref.…”
Section: Composition Of Oxygen Precipitatesmentioning
confidence: 99%
“…It is also impossible to study the morphology of oxygen precipitates by FTIR which is easily possible in moderately doped wafers. [7,8] In order to overcome the problems appearing during investigation of highly doped wafers one uses advanced investigation methods and etching solutions.…”
Section: Introductionmentioning
confidence: 99%